Latex vascular injection as method for enhanced neurosurgical training and skills - Pérez-Cruz, Julio C.; Macías-Duvignau, Mario A.; Reyes-Soto, Gervith; Gasca-González, Oscar O.; Baldoncini, Matias; Miranda-Solís, Franklin; Delgado-Reyes, Luis; Ovalles, Carlos; Catillo-Rangel, Carlos; Goncharov, Evgeniy; Nurmukhametov, Renat; Lawton, Michael T.; et al. (Frontiers in Surgery, 2024)
Background: Tridimensional medical knowledge of human anatomy is a key step in the undergraduate and postgraduate medical education, especially in surgical fields. Training simulation before real surgical procedures is necessary to develop clinical competences and to minimize surgical complications.Methods: Latex injection of vascular system in brain and in head-neck segment is made after washing out of the vascular system and fixation of the specimen before and after latex injection.Results: Using this latex injection technique, the vascular system of 90% of brains and 80% of headneck segments are well-perfused. Latex-injected vessels maintain real appearance compared to silicone, and more flexible vessels compared to resins. Besides, latex makes possible a better perfusion of small vessels.Latex vascular injection technique of the brain and head-neck segment is a simulation model for neurosurgical training based on real experiencing to improve surgical skills and surgical results.